Nutritional habits in children – research on health-related habits in schoolchildren in the Republic of Serbia in 2017 - Đorđević, Slavica; Knežević, Snežana; Jovanović, Verica (General Practice, 2023)
Introduction. Childhood nutritional habits may have a tremendous influence on long-term health. Nutritional habits developed during childhood may turn into a lifetime habit. Missed meals, skipping breakfast, and increased intake of sweets are related to overweight and obesity. Aim. We aimed to research nutritional habits in schoolchildren in Serbia. Method. We used the data from the research “Healthrelated habits in schoolchildren in Serbia in 2017”. We used the standardized international protocol of the World Health Organization for data gathering. We polled 3.933 participants, aged 11, 13, and 15. Results. The habit of having breakfast, on shooldays days, shows statistically significant difference around regions, for ages 11 (p = 0,001) and 13 (p = 0,000). At the age of 11 (p = 0,046), the majority of children have breakfast on weekends in Belgrade (92,7%). When fruit consumption is concerned, the regions statistically significantly differ for the age 11 (p = 0,006). The greatest consumption of fruit is found in the region of Vojvodina (37,4%). In Belgrade, 5% of children never eat vegetables. At the age of 15, there is a statistically significant difference (p = 0,046) in vegetable consumption. Most vegetables are consumed in South and East Serbia (25,5%), and Sumadija and West Serbia (27,4%). There is a statistically significant difference (p=0,016), at the age of eleven, in sweets consumption, among regions. There are the least children who never consumed sweets (1,8%) in Vojvodina. Conclusion. Based on analyzed data, we concluded that children aged eleven, thirteen, and fifteen, in the Republic of Serbia, don`t eat quite healthy. The results may be useful for the promotion of health-educational programs, which, in turn, may lead to behavioral changes.